PERAN GURU DALAM MEMBENTUK KARAKTER PERCAYA DIRI ANAK USIA DINI - H.M. Taufik Amrillah; Yosi Yulizah; Dini Widiyanti (Jurnal Literasiologi, 2022)
This study discusses the role of teachers in shaping self-confidence in early childhood. The teacher is the main role in shaping the character of each child, this shows the teacher must be able to carry out his main role as a guide, motivator, and inspiration. The purpose of this study was to identify and describe the teacher's role in shaping the self-confident character of early childhood. By using qualitative research methods using descriptive qualitative which is defined by describing, with this research is to describe a situation with words. This is very much in line with the problem being studied, because this study analyzes phenomena and facts regarding the role of teachers in shaping the self-confident character of early childhood. With the results of the research that has been analyzed, it is found that the teacher has become a teacher who acts as a guide, motivator, and inspiration during the learning process in the classroom.